Participants in Treponema pallidum pathogenesis: progress in functional proteins - Zuo, Wei; Xiao, Yongjian; Xiang, Qing; Xiao, Shuangwen; Xie, Yafeng (Frontiers in Immunology, 2025)
Treponema pallidum subsp. pallidum (T. pallidum) is the causative agent of syphilis, a chronic sexually transmitted disease that leads to widespread organ damage. The pathogenesis of syphilis involves crucial functional proteins that facilitate bacterial adhesion to host cells, invasion, dissemination, immune evasion, and inflammatory responses. Investigating these proteins is crucial for the development of innovative diagnostic tools, vaccines, and therapies. However, the intricate nature of T. pallidum and the inability to culture in vitro hinder our comprehensive understanding of these proteins. This review article presents innovative understandings of the pathogenesis of T. pallidum functional proteins, building upon existing knowledge. This paper establishes a foundation for comprehending the current knowledge landscape and outlining future research avenues.